Social network sites: information disclosure, perceived vulnerability, privacy concerns and perceived benefits - Salleh, Norsaremah; Hussein, Ramlah; Mohamed, Norshidah; Abdul Karim, Nor Shahriza; Ahlan, Abdul Rahman; Aditiawarman, Umar (2012)
People have been using Social Network Sites (SNS) to communicate and make friends through online. Although SNS offer many benefits to the users, information privacy seemed to be overlooked. Based on iire protection motivation theory' this study investigated the factors that might influence youth to disclose information about themselves on the SNS. Using university students as sample, we found that perceived vulnerability, benefits and self efficacy are significantly related to information disclosure.